Investigation of cytotoxic effect of black mulberry (Morus nigra L.) fruit - Dalkilic, S.; Dalkilic, L. K.; Inci, S.; Korkmaz, I; Kirbag, S. (Natl Inst Science Communication-Niscair, 2021)
The aim of this study was to determine the cytotoxic effect of black mulberry fruit extract (Morus nigra L.) on human breast cancer (MDA-MB-231) and prostate cancer (PC3) cell lines. The extract prepared from mulberry (M. nigra) fresh fruit was applied to cancer cell lines in 5 different v/v concentrations (10%, 4%, 2%, 1.33% and 1%) for 72 h. At the end of the incubation period, cell viability was determined by MTT [3- (4,5-dimethylthiazol-2-yl) -2,5-diphenyltetrazolium bromide] assay. Results were compared with negative and positive control groups. The effect of mulberry (M. nigra) fruit extract on cell viability was determined depending on the concentration applied; extract showed a significant cytotoxic effect on PC3 cell line at the 10% concentration compared to the control group, but not detected any effect at 4%, 2%, 1.33% and 1% concentrations. In the MDA-MB-231 cell line, there was a high cytotoxic effect at a concentration of 10% compared to the control group, while a lower effect was observed at 4%, 2%, 1.33% and 1% concentrations. The data obtained from the study showed that extract prepared from black mulberry fruit has cytotoxic effect especially against breast cancer cells.
Keywords: Breast cancer; Cytotoxicity; Morus nigra L.; MTT; Prostate cancer